2023
DOI: 10.1097/corr.0000000000002662
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Pain Reduction and Functional Improvement Among Splint Alone, Steroid Alone, and Combination for the Treatment of Adults With Trigger Finger?

Abstract: Background Steroid injection and splinting, which are commonly recommended nonsurgical treatments in adults with trigger finger, have been demonstrated to effectively relieve pain and improve function. However, to our knowledge, there have been no direct comparisons of pain relief and function improvement with splinting alone, steroid injection alone, or a combination of splinting and steroid injection in patients with this diagnosis. Question/purpose A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…One specific finding of Atthakomol et al’s trial that I found intriguing is that splinting adherence did not alter the degree of improvement at 52 weeks [1]. This was not a primary study analysis, and it is also possible that all patients within this trial were adherent “enough” for positive outcomes (although this then calls into question the minimum necessary wearing schedule).…”
Section: Where Do We Need To Go?mentioning
confidence: 92%
See 4 more Smart Citations
“…One specific finding of Atthakomol et al’s trial that I found intriguing is that splinting adherence did not alter the degree of improvement at 52 weeks [1]. This was not a primary study analysis, and it is also possible that all patients within this trial were adherent “enough” for positive outcomes (although this then calls into question the minimum necessary wearing schedule).…”
Section: Where Do We Need To Go?mentioning
confidence: 92%
“…Atthakomol et al’s [1] findings provide additional support for splinting as a first-line treatment option for adult single-digit trigger finger. While there has been evidence supporting splinting as an option for decades, a survey of U.S. hand surgeons revealed that only a minority prefer splinting alone for nonoperative management [10].…”
Section: Where Are We Now?mentioning
confidence: 97%
See 3 more Smart Citations